Cognitions and Practices of Iranian ELT Instructors and Content Teachers in Teaching Discipline-Based EAP Courses: A Replication Study - Fatemeh Soleimani; Ahmad Alibabaee (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Although research studies on methodological issues of English for General Purposes are abundant in the literature, they are still one of the less explored areas of research in English for Academic Purposes, especially with respect to teachers’ cognitions and practices. Also, lack of collaboration between ELT instructors and content teachers in teaching discipline-based EAP courses has resulted in noticeable inconsistencies in the two groups’ instructions. The present study was an extension of Atai and Fatahi-Majd (2014) and explored the cognitions and practices within and across six Iranian ELT instructors and six content teachers regarding their translation-based, form focused, feedback and vocabulary teaching activities. Each participant was observed for six sessions. Field note taking and semi-structured interviews were also done with the two groups of teachers so as to delve into the cognitions underlying their actual practices. The general findings supported Atai and Fatahi (2014) in all the areas under investigation where there were within group inconsistences and across-group discrepancies within and between the two groups of teachers respectively with content teachers being much more inconsistent than ELT instructors in terms of their practices and cognitions. The findings of the study have implications for renewing the current practices of ELT instructors and content teachers teaching discipline-based EAP courses worldwide.